2011
DOI: 10.1186/1479-5876-9-163
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression levels and genetic status of genes involved in the EGFR and NF-κB pathways in metastatic non-small-cell lung cancer patients

Abstract: BackgroundMetastatic non-small-cell lung cancer (NSCLC) has a dismal prognosis. EGFR is overexpressed or mutated in a large proportion of cases. Downstream components of the EGFR pathway and crosstalk with the NF-κB pathway have not been examined at the clinical level. We explored the prognostic significance of the mRNA expression of nine genes in the EGFR and NF-κB pathways and of BRCA1 and RAP80 in patients in whom EGFR and K-ras gene status had previously been determined. In addition, NFKBIA and DUSP22 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…It could be of interest to examine the EZH2:BRCA1 mRNA ratio in SCLC patients, although in the report by the Heymach group ( 3 ), it seems that BRCA1 and EZH2 could both be overexpressed. In our experience, the expression of both BRCA1 and EZH2 was signifi cantly higher in SCLC than in NSCLC patient tumors ( 11 ). Therefore, the inverse relationship observed in breast cancer may not hold true for SCLC.…”
Section: A Genetic Snapshot Of Small Cell Lung Cancermentioning
confidence: 73%
“…It could be of interest to examine the EZH2:BRCA1 mRNA ratio in SCLC patients, although in the report by the Heymach group ( 3 ), it seems that BRCA1 and EZH2 could both be overexpressed. In our experience, the expression of both BRCA1 and EZH2 was signifi cantly higher in SCLC than in NSCLC patient tumors ( 11 ). Therefore, the inverse relationship observed in breast cancer may not hold true for SCLC.…”
Section: A Genetic Snapshot Of Small Cell Lung Cancermentioning
confidence: 73%
“…In literature, there is only one report showing that low levels of MTDH also occur in pathological conditions (Santarpia et al, 2011). As demonstrated by Santarpia et al in metastatic NSCLC, patients with low levels of both BRCA1 and AEG-1 showed significant improved progression-free survival (PFS) compared to those with…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that establishing the presence of the T790M mutation and BRCA1 levels could aid appropriate treatment selection for such patients [25]. Furthermore, the coexpression of BRCA1 and the associated oncogene, astrocyte elevated gene-1, could represent a marker for prognosis in patients with wild-type EGFR and response to erlotinib treatment in patients with EGFR mutations [30].…”
Section: Basal T790m Mutationsmentioning
confidence: 99%